2019
DOI: 10.1155/2019/9542857
|View full text |Cite
|
Sign up to set email alerts
|

Pruritic Crusted Scabies in an Immunocompetent Infant

Abstract: Crusted scabies (also known as Norwegian scabies) is a highly contagious variant of scabies characterized by profuse proliferation of mites in the skin and widespread, crusted, hyperkeratotic papules, plaques, and nodules. Typically, pruritus is minimal or absent. The condition usually occurs in immunocompromised individuals. Occurrence in healthy infants has rarely been reported. We report an 11-month-old healthy Malay boy who presented with crusted scabies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Crusted scabies has rarely been described in healthy infants. 2,3 The presence of an immature immune system, difficulty in scratching (mite elimination mechanism), overcrowding, or malnutrition may be predisposing factors. 3 The use of systemic or topical corticosteroids as well as calcineurin inhibitors has been associated with its development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Crusted scabies has rarely been described in healthy infants. 2,3 The presence of an immature immune system, difficulty in scratching (mite elimination mechanism), overcrowding, or malnutrition may be predisposing factors. 3 The use of systemic or topical corticosteroids as well as calcineurin inhibitors has been associated with its development.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors include neurological disease, intellectual disability, malignant neoplasms, and immune disorders. Crusted scabies has rarely been described in healthy infants 2,3 . The presence of an immature immune system, difficulty in scratching (mite elimination mechanism), overcrowding, or malnutrition may be predisposing factors 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Nails are often thickened, discoloured, and dystrophic. Pruritus may be minimal or absent [ 6,7], while in the immunocompetent host, it has been reported that lesions were intensively pruritic [7].…”
Section: Discussionmentioning
confidence: 99%